Cytologic features of ovarian granulosa cell tumors in pleural and ascitic fluids. Issue 7 (21st January 2015) - Omori, Makiko; Kondo, Tetsuo; Yuminamochi, Tsutomu; Nakazawa, Kumiko; Ishii, Yoshio; Fukasawa, Hiroko; Hashi, Akihiko; Hirata, Shuji
<x xml:space="preserve">Abstract</x> Adult granulosa cell tumor (AGCT) is an uncommon neoplasm of the ovary with potential for aggressive behavior and late recurrence. The most important prognostic factor for AGCT is tumor stage. Thus, cytological assessment of pleural or ascitic fluids is crucial for initial staging and subsequent patient management. We report herein two cases of ovarian AGCT presenting with exfoliated tumor cells in pleural and ascitic fluid. The first case involved a 61‐year‐old woman who presented with stage Ic (a) AGCT. Seven years after initial diagnosis, pleural effusion and pleural dissemination were identified. The second case involved a 50‐year‐old woman who presented with stage IV AGCT with massive ascites and right pleural effusion. Fluid cytology from both cases showed cohesive or loose clusters of small uniform neoplastic cells with round‐to‐oval nuclei, coffee‐bean‐shaped nuclear grooves, small nucleoli, and scant cytoplasm. Call‐Exner bodies were also observed in these cytologic specimens. In the differential diagnosis of small monomorphic tumor cells in pleural effusion or ascites, coffee‐bean‐shaped nuclear grooves and cell clusters forming Call‐Exner bodies are diagnostic clues of AGCT. Diagn. Cytopathol. 2015;43:581–584. © 2015 Wiley Periodicals, Inc.